Phytoremedial Wreath: a Traditional Excellence of Healing - Pandey, Hari Prakash; Verma, B. K. (Indian Forester, 2005)
In India, traditional medicines have had a glorious past, an absorbing present and promise to enjoy an exdting future. Indian scholars have not only developed conventional healing methods but also acquired a great many non-conventional healing excellence. In this piece of work a marvellous aspect of ethnobotany, 'remedy through plant wreath' has been explored out from the aboriginals of sub-Himalayan Tarai region of Uttar Pradesh, India. The communication provides an enumeration of 16 plants with their pharmacognostic features and uses in a novel way with clinical confirmations in some cases.